Química e bioquímica quântica do agrotóxico imidacloprido: o matador de abelhas - Moreira, Antônio Aurélio Gomes (2017)
Insect pest damage in agriculture are a historical problem. The development of science fields enabled the manufacture of efficient products to the pest control. Imidacloprid, the first insecticide from neonicotinoid class, is one of the largest chemical consumed on the global crop protection market. However, the imidacloprid has been blamed to cause the death of beneficial insects such as pollinator bees. The structural and electronic properties of imidacloprid are essential for understanding the interaction mechanism with amino acids residues from nicotinic acetylcholine receptors (nAChRs). In this work, the conformational analysis of the imidacloprid molecule was carried out within the Density Functional Theory (DFT) approach employing either M06 2X and B3LYP functional (gas phase and PCM solvation model), in Gaussian 09 code. The energy of the crystalline unit cell was minimized using the LDA-CAPZ and GGA-PBE-TS parametrizations, implemented in the CASTEP code. The structural, electronic, optical and vibrational properties of either imidacloprid molecule and crystal were calculated and compared to the experimental data. Besides, we have assessed the interaction between imidacloprid molecule and the amino acids residues from the acetylcholine binding protein (AChBP) of freshwater Aplysia californica (AChBP), which is homologous to the nAChRs receptors. The interaction energies were carried out within the DFT framework by applying the GGA-PW91-OBS parameterization implemented in Dmol3 code; we have used the COSMO solvation model. The binding domain AChBP was split according to the molecular fragmentation with conjugated caps (MFCC) scheme. The interaction energies calculations were performed considering a fixed value of dielectric constant and a variable value as well. The conformational analysis performed with the M06-2X functional provided four structures (one gas phase structure and three in the PCM model); otherwise, we have obtained two conformers in the gas phase and two in the PCM model as a result from B3LYP functional. The Hirshfeld population analysis (HPA) showed that imine nitrogen atom to presents the largest negative charge; while natural population analysis (NPA) has indicated that the secondary nitrogen from the imidazole ring possesses the largest negative charge. Some researchers have assumed that the tertiary nitrogen from the imidazole ring is partially positive charged, however, we have found the charges -0.04e, according to the HPA, and 0,48e as a result from NPA. The bond lengths from the guanidine and nitro moieties were all inferior to the usual bond lengths, suggesting a high degree of electron delocalization. The HOMO (LUMO) orbital is located in the imidazole and chloropyridyne rings (nitro and guanidine groups). The theoretical infrared and Raman spectra obtained from either M06-2X and B3LYP functionals were helpful to the assign the most intense experimental bands. The deconvolution of optical absorption spectrum suggests that the first excitation energy occurs at 4.11 eV; the theoretical calculations predicted that this absorption line is related to the orbital transition H-8 -> L0 (M06-2X) and H0 -> L0 (B3LYP). The main experimental absorption line, at 4.56 eV, occurs owing the transition between the orbitals H0 -> L0 (M06 2X) and H2 -> L0 (B3LYP). The analysis of band structure showed that the energy levels at the top of the valence band and the lower region of the conduction band are originated from the nitrogen p orbitals; the direct band gap is 2.72 eV. Using the Tauc model, the absorption spectrum fitting method was employed to estimate the optical direct band gap (3.50 eV). The complex dielectric function showed that the fundamental absorption edge starts at 2.62 eV. Infrared and Raman experimental bands were assigned by comparing the experimental spectra with the vibrational lines calculated to the crystal. According to the MFCC method, the most relevant residues from chain B that interact with imidacloprid are Trp147 (-19.16 kcal mol-1) and Tyr188 (-14.02 kcal mol-1); while the most relevant residues from chain A are Ile118 (-16.97 kcal mol-1) and Tyr55 (-5.34 kcal mol-1); other relevant residues to the imidacloprid interaction encompasses Ser189, Val148, Cys190, Cys191, Ile106. The shielding promoted by the side residues (caps) significantly influence the interaction energy, hence the MFCC method is a feasible low-cost computational tool.